A contextual model of self-regulation change mechanisms among individuals with addictive disorders. (November 2017) - Roos, Corey R.; Witkiewitz, Katie
Abstract: Numerous behavioral treatments for addictive disorders include components explicitly aimed at targeting self-regulation (e.g., coping and emotion regulation). We first provide a summary of key findings to date among studies that have examined self-regulation as a mechanism of behavior change (MOBC) in behavioral treatments for addictive disorders. Based on our review, we conclude that the role of self-regulation as a MOBC across behavioral treatments for addictive disorders is not well-characterized and findings are inconsistent across studies. For example, our review indicates that there is still inconsistent evidence that coping is a unique MOBC in cognitive-behavioral approaches for addictive behaviors. We propose that there has been slow progress in understanding self-regulation as a MOBC in addiction treatment because of a lack of attention to contextual factors. Accordingly, in the second half of this paper, we propose a contextual model of self-regulation change mechanisms, which emphasizes that the role of various facets of self-regulation as MOBC may depend on contextual factors in the immediate situational context (e.g., fluctuating internal and external cues) and in the broader context in which an individual is embedded (e.g., major life stressors, environmental conditions, dispositions). Additionally, we provide specific recommendations to guide future research for understanding both between-person and within-person self-regulation MOBC in addiction treatment. In particular, we provide key recommendations for how to capitalize on intensive longitudinal measurement methods (e.g., ecological momentary assessment) when bringing a contextual perspective to the study of self-regulation as MOBC in various addiction treatments. Highlights: There has been slow progress in understanding self-regulation as a mechanism of change in behavioral treatments for addiction. We contend that slow progress is likely due to a lack of attention to context. We propose a contextual model of self-regulation change mechanisms. This model emphasizes that the role of self-regulation as a mechanism of change may depend on a range of contextual factors. We provide specific recommendations to guide future empirical research on the role of self-regulation in addiction treatment.